2011
DOI: 10.2478/v10015-011-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Do Marked Topics Enhance Memory?

Abstract: Do Marked Topics Enhance Memory? We examined the effects of markedness, the deviation from the canonical Subject-Verb-Object structure in English, on the memory of listeners for the topic of the sentence. We used three marked topic constructions: Left-Dislocation, Object-Fronting, and Subject-Marking. Sentences with these structures were inserted as the 6th item in lists of 12 canonical sentences. In all sentences the topic was the name of a man. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For English, Netz, Eviatar, and Kuzar (2011) report an auditory recall experiment where they found that an element that appears in a left-dislocated position as Thomas in Thomas, he found Susan is recalled better than an element that is 'topicalised' (= fronted) as in Thomas, Susan found, and also better than a clause-initial element that is not separated syntactically but only prosodically from the remainder of the clause, as in Thomas, found Susan. However, this study has several limitations.…”
Section: Hypothesis 4: Information Structure In Left-dislocation Strumentioning
confidence: 90%
“…For English, Netz, Eviatar, and Kuzar (2011) report an auditory recall experiment where they found that an element that appears in a left-dislocated position as Thomas in Thomas, he found Susan is recalled better than an element that is 'topicalised' (= fronted) as in Thomas, Susan found, and also better than a clause-initial element that is not separated syntactically but only prosodically from the remainder of the clause, as in Thomas, found Susan. However, this study has several limitations.…”
Section: Hypothesis 4: Information Structure In Left-dislocation Strumentioning
confidence: 90%